2018
DOI: 10.1210/jc.2018-00968
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Dedifferentiation in Patients With T2D With Adequate Glucose Control and Nondiabetic Chronic Pancreatitis

Abstract: The data support the view that pancreatic β-cells are dedifferentiated in patients with T2D with adequate glucose control. Furthermore, the existence of abundant dedifferentiated cells in NDCP suggests that inflammation-induced β-cell dedifferentiation can be a cause of pancreatogenic diabetes during disease progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 49 publications
7
72
0
Order By: Relevance
“…They also found a decrease in the number of insulin‐positive cells expressing the transcription factors FOXO1 and NKX6.1, which characterize functional β cells, and an increased expression of these markers in glucagon‐positive and somatostatin‐positive islet cells. A recent study reported a similar threefold increase in the number of hormone‐negative endocrine cells in islets of T2D patients with normal fasting glycemia . Interestingly, this study detected a comparable fraction of dedifferentiated endocrine cells in islets of patients with nondiabetic chronic pancreatitis, which correlated with pathological findings of inflammatory cell infiltration, fibrosis, and atrophy.…”
Section: Possible Mechanisms Of β‐Cell Dedifferentiationsupporting
confidence: 80%
“…They also found a decrease in the number of insulin‐positive cells expressing the transcription factors FOXO1 and NKX6.1, which characterize functional β cells, and an increased expression of these markers in glucagon‐positive and somatostatin‐positive islet cells. A recent study reported a similar threefold increase in the number of hormone‐negative endocrine cells in islets of T2D patients with normal fasting glycemia . Interestingly, this study detected a comparable fraction of dedifferentiated endocrine cells in islets of patients with nondiabetic chronic pancreatitis, which correlated with pathological findings of inflammatory cell infiltration, fibrosis, and atrophy.…”
Section: Possible Mechanisms Of β‐Cell Dedifferentiationsupporting
confidence: 80%
“…We and others have proposed that β cell failure arises from β cell dedifferentiation, i.e., loss of mature β cell features associated with regression to a progenitor-like stage (6)(7)(8)(9)(10). This process accounts for the partial clinical reversibility of β cell dysfunction (8,(11)(12)(13)(14)(15)(16) and has been found to variable extents (17) in autopsy surveys of diabetic patients (18,19). In addition, it may explain the observation of mixed-features α/β cells in humans (20) and lineage conversion in rodents (7), which dovetail with the increased glucagon "tone" in diabetes (21).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic link between T2D GWAS loci, β cell maintenance transcription factors, and superenhancers is elusive. A glaring gap in knowledge in this area relates to FoxO1, a key factor involved in the pathogenesis of islet β cell dysfunction in rodents and humans (14)(15)(16), whose role in diabetes-associated superenhancers and human GWAS loci has not been investigated (12,17). This gap in knowledge can be attributed to the difficulty of monitoring the localization of endogenous FoxO1 in vivo which, combined with the low efficiency of antibodies to immunoprecipitate FoxO1, have hampered efforts to catalog its genomic targets.…”
mentioning
confidence: 99%